2018
DOI: 10.7717/peerj.4390
|View full text |Cite
|
Sign up to set email alerts
|

16S rRNA gene sequencing reveals effects of photoperiod on cecal microbiota of broiler roosters

Abstract: Photoperiod is an important factor in stimulating broiler performance in commercial poultry practice. However, the mechanism by which photoperiod affects the performance of broiler chickens has not been adequately explored. The current study evaluated the effects of three different photoperiod regimes (short day (LD) = 8 h light, control (CTR) = 12.5 h light, and long day (SD) = 16 h light) on the cecal microbiota of broiler roosters by sequencing bacterial 16S rRNA genes. At the phylum level, the dominant bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…In fact, knowing the main microbiota composition during the growing period and how management practices could influence its modulation could help quick decisions be taken at farm level [ 46 , 47 ]. In this sense, it might be interesting to consider microbiota composition as a biomarker of poultry health and productive performance [ 7 , 9 , 48 ]. It is well demonstrated that a greater complexity of the gut microbiota is observed as animals grow [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, knowing the main microbiota composition during the growing period and how management practices could influence its modulation could help quick decisions be taken at farm level [ 46 , 47 ]. In this sense, it might be interesting to consider microbiota composition as a biomarker of poultry health and productive performance [ 7 , 9 , 48 ]. It is well demonstrated that a greater complexity of the gut microbiota is observed as animals grow [ 49 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of some of these factors on productive performance of broiler chickens has been widely studied [38], but there are still few studies that analyze these relationships based on the composition and diversity of the intestinal microbiota. Among the most relevant farm management factors, stand out the production system, particularly the choice of alternative production systems with access to range [4,39,40]; the hygiene and biosecurity programs, the protocols and criteria used to define the time of feed access, feed processing, and feeding programs [41,42,43], the protocols and criteria used to define the vaccination schemes, therapeutic medication and rotation of the antibiotic growth promoters throughout the year, factors associated with the stress and welfare of the birds, such as the stocking density [44,45], duration of photoperiod [46,47], ventilation and ammonia concentration in the air [48,49] and heat-stress [50,51]. It is clear that management decisions define the microbiota in the environment that surrounds the birds and therefore the intestinal microbiota, but more studies are needed under commercial conditions to determine the key points that contribute to maintaining a healthy intestinal microbiota and maximize chicken productivity.…”
Section: Key Factors That Shape Chicken Gut Microbiotamentioning
confidence: 99%
“…Past studies suggest that there may be sex differences in the gut microbiome's response to photoperiod, though to varying degrees (Bailey et al, 2010;Davenport et al, 2014;Hieke et al, 2019;Wang et al, 2018). In the current study, photoperiod differentially affected bacterial diversity and the relative abundance of bacteria in the male and female gut, further suggesting that the gut microbiome may play a role in sex-specific seasonal changes.…”
Section: Seasonal Changes and Sexual Dimorphism In The Gut Microbiomementioning
confidence: 99%
“…In addition, other studies suggest that the gut microbiome changes on a seasonal basis. For example, chickens and mice exhibit seasonal shifts in the gut microbiome (Cui et al, 2016;Hieke et al, 2019;Wang et al, 2018). Further, body mass correlates with the relative abundance of Proteobacteria, Citrobacter and Firmicutes in LD male Siberian hamsters (Bailey et al, 2010).…”
Section: Introductionmentioning
confidence: 99%